The wedding - Steel, Danielle (Bantam Press, 2000)
Summary: Allegra Steinberg has all the real-life problems of a Hollywood mover and shaker. As the daughter of two prominent producers and the entertainment lawyer for some of the most famous stars, Allegra spends her time supporting those who stand directly in the glare of fame. When Allegra's fragile personal life starts to crumble, however, she finds the courage to turn her attentions to her own life. And when she meets Jeff Hamilton, a sincere, sexy writer, she finds a reason for self-examination. The course of true love soon takes its required detours, and Jeff and Allegra must learn to compromise, grow up, and grow together.